Blinatumomab consolidation and maintenance therapy in adults with relapsed/refractory B-precursor acute lymphoblastic leukemia - Rambaldi, Alessandro; Huguet, Francoise; Zak, Pavel; Cannell, Paul; Tran, Qui; Franklin, Janet; Topp, Max S (Blood advances, 2020)
In a phase 3 clinical study of heavily pretreated adults with relapsed/refractory (R/R) acute lymphoblastic leukemia (ALL), overall survival (OS) following blinatumomab, a BiTE (bispecific T-cell engager) immunooncology therapy, was significantly improved vs chemotherapy following induction (cycles 1 to 2). Here we report the efficacy and safety of those who received additional cycles of blinatumomab. Blinatumomab was administered as a continuous IV infusion for 4 weeks in a 6-week cycle. Patients who achieved a bone marrow response (≤5% blasts) or complete remission (full, partial, or incomplete hematological recovery) during induction could receive additional cycles of blinatumomab. OS and relapse-free survival (RFS) for consolidation (cycles 3 to 5) vs no consolidation, and maintenance (cycles ≥6) vs no maintenance were analyzed using Simon-Makuch and Mantel-Byar odds ratios. Of 267 patients who received blinatumomab induction, 86 (32%) entered consolidation and 36 (13%) entered maintenance. Evidence of longer OS was demonstrated among the maintenance group compared with no-maintenance (median OS [95% confidence interval, CI]: not reached for maintenance vs 15.5 months for no maintenance). Median RFS (months; 95% CI) was numerically longer among maintenance group (14.5; 7.1 to 21.9) compared with no-maintenance (9.8; 8.5 to 11.1). A lower incidence of adverse events was seen during maintenance (72.2%) compared with induction (97.2%) and consolidation (86.1%). Adults with R/R ALL who achieved remission following blinatumomab induction had longer survival on continuation therapy than those who discontinued blinatumomab early, supporting the use of blinatumomab as long-term therapy. No new safety signals were reported. This trial was registered at www.clinicaltrials.gov as #NCT02013167.
Keywords: protilátky bispecifické; Antineoplastic Agents; lidé; Adult; protinádorové látky; akutní lymfatická leukemie; dospělí; konsolidační chemoterapie; Antibodies, Bispecific; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Consolidation Chemotherapy; Humans